Overcoming water scarcity and quality constraints: Markets for Tradable Water Rights - Kemper, Karin E. (International Food Policy Research Institute, 2001)
Water markets have been advocated as a means of improving water resources management by increasing the efficiency of water use and allocation within and among sectors. Water markets are more flexible than command-and-control instruments in moving water to higher-valued uses in a manner agreeable to all parties, thus promoting economic growth and diminishing social tension from competition for scarce water resources.